Tunable non‐Hermitian skin effects in Su‐Schrieffer‐Heeger‐like models - Wu, Shi-Qiao; Xu, Yadong; Jiang, Jian-Hua (Frontiers in Physics, 2023)
Skin effect is a well-known feature of non-Hermitian systems, in which the bulk states evolve from extended to localized toward system boundaries. In this work, we numerically reveal tunable non-Hermitian skin effects in one and two-dimensional Su-Schrieffer-Heeger (SSH)-like tight-binding models. Their occurrence mainly relies on both of the non-reciprocal hoppings within and across the unit cells. Notably, we demonstrate that by engineering the non-reciprocal hopping configurations of lattice sites, the non-Hermitian skin modes can be predicted at expected edges or corners irrespective of whether the system is topological or not. And they also have no relation with the concrete value of hopping terms but with their scaling factors. These tunable non-Hermitian skin effects and higher-order non-Hermitian skin effects can be exploited to guide waves into targeted regions and may have useful applications when realized in metamaterials